The “greening” of financial public law: reality and margins of progress - Emilie Moysan (Prawo Budżetowe Państwa i Samorządu)
Having in mind concerns on climate change, that theme occupies an increasing place in French legal order, in particular in public financial law. Current events provide a perfect illustration of this with an implementation of a “green budget”: a mechanism allowing a new classification of budgetary and tax expenditures according to their environmental impact on the one hand, and better identification of environmental revenues on the other hand. This new system should not obscure a variety of financial tools put in place by the State, sometimes for several years, whether expenditure or revenue, to fight against climate change. However, the fact remains that the ambition of the French State is not, as it stands, sufficient to respond to the climate emergency, which requires the emergence of new public financial engineering.